MODERN EDUCATION AND GLOBALIZATION THE INNOVATIVE COMPETENT-FOCUSED TECHNOLOGIES - Elena, Sheremetyeva; Tatiana, Stepanova (Journal of Humanity, 2013)
The article is devoted to modern problems of the world development in education. One of the key elements of the national innovative education system â the competent-focused educational technologies â with reference to Samara Institute of the Russian State University of Trade and Economics is given special attention.